"But that was meant to be a compliment!": Evaluative costs of confronting positive racial stereotypes. (August 2019) - Alt, Nicholas P.; Chaney, Kimberly E.; Shih, Margaret J.
Past research on confronting racial prejudice has largely examined negative racial stereotypes. In the present work, we investigate perceiver and target perspectives associated with the evaluative costs of confronting positive racial stereotypes. We demonstrate that, in general, Asian Americans and African Americans who confront positive racial stereotypes suffer higher evaluative costs compared to targets who confront negative racial stereotypes and those who do not confront due, in part, to the lower perceived offensiveness of positive stereotypes (Studies 1 and 2). Moreover, Asian American and African American participants report lower confrontation intentions and higher anticipated evaluative costs for confronting positive, compared to negative, stereotypes. Furthermore, higher perceived offensiveness and lower anticipated favorable evaluations serially mediate the relationship between stereotype valence and confrontation intentions (Study 3). Overall, this research extends our understanding of the evaluative costs associated with confronting prejudice, with important downstream consequences regarding the continued prevalence of positive racial stereotypes.